2006
DOI: 10.1259/dmfr/31981949
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of zoomed digital image in the detection of periodontal bone defect:in vitrostudy

Abstract: Objectives: (1) To evaluate the intraobserver agreement related to image interpretation and (2) to compare the accuracy of 100%, 200% and 400% zoomed digital images in the detection of simulated periodontal bone defects. Methods: Periodontal bone defects were created in 60 pig hemi-mandibles with slow-speed burs 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm and 3.0 mm in diameter. 180 standardized digital radiographs were made using Schick sensor and evaluated at 100%, 200% and 400% zooming. The intraobserver agreement was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…To simulate soft tissues, we used five types of materials in three diverse thicknesses. Both material type and thickness have been widely used 2,5,6,9,10,15,16 with aims to simulate the real anatomical structures. 27,28 In this study, we showed that both the material type and the thickness tested influenced the gain of density in bone tissue as demonstrated by DSR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To simulate soft tissues, we used five types of materials in three diverse thicknesses. Both material type and thickness have been widely used 2,5,6,9,10,15,16 with aims to simulate the real anatomical structures. 27,28 In this study, we showed that both the material type and the thickness tested influenced the gain of density in bone tissue as demonstrated by DSR.…”
Section: Discussionmentioning
confidence: 99%
“…3 The use of soft-tissue simulation materials having densities similar to the tissues found in patients in a real environment helps avoid exposure of patients to excessive radiation during in vivo studies. 4 Based on literature, the use of soft-tissue simulators, such as acrylic plates, 2,4-8 wax, 2,4,9,10 water, 11-14 wood 4,15,16 and bovine tissue 17 has been tested in different ways with respect to the nature and/or the thickness of the material put around dry mandibles. 2,5,16 It is important that these simulation materials are accurately reproducible, measurable and are ready for use in any circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was carried out on two-dimensional radiographs. Measurements from conventional or digital radiographs do not accurately reflect the clinical situation, so they usually result in underestimation 6 . It is plausible that the residual defect the authors measured was actually an underestimation of clinical reality.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of magnification on the diagnostic accuracy of two-dimensional digital radiography have also been the subject of several studies. [12][13][14][15][16][17][18][19] According to the literature; no study has assessed the accuracy of linear measurements made on CBCT scans with different image magnifications. Therefore, this study aimed to assess the effects of image magnification on the accuracy of linear measurements made by New Tom VGi CBCT device (New Tom VGi, Quantitative Radiology, Verona, Italy).…”
Section: Introductionmentioning
confidence: 99%